Physiological and transcriptional responses to inorganic nutrition in a tropical Pacific strain of Alexandrium minutum: Implications for the saxitoxin genes and toxin production - Kieng, Soon Hii; Po, T.L; Nyuk, Fong Kon; Yoshinobu, Takata; Gires, Usup; Chui, P.L (Elsevier Ltd., 2016)
Saxitoxins (STXs) constitute a family of potent sodium channel blocking toxins, causative agents of paralytic shellfish poisoning (PSP), and are produced by several species of marine dinoflagellates and cyanobacteria. Two STX-core genes, sxtA and sxtG, have been well elucidated in Alexandrium but the expression of these genes under various nutritional modes in tropical species remains unclear. This study investigates the physiological responses of a tropical Pacific strain of Alexandrium minutum growing with nitrate or ammonium, and with various nitrogen to phosphorus (N:P) supply ratios. The transcriptional responses of the sxt genes were observed. Likewise, a putative sxtI encoding O-carbamoyltransferase (herein designated as AmsxtI) was recovered from the transcriptomic data, and its expression was investigated. The results revealed that the cellular toxin quota (Qt) was higher in P-depleted, nitrate- grown cultures. With cultures at similar N:P (<16), cells grown with excess ammonium showed a higher Qt than those grown with nitrate. sxtA1 was not expressed under any culture conditions, suggesting that this gene might not be involved in STX biosynthesis by this strain. Conversely, sxtA4 and sxtG showed positive correlations with Qt, and were up-regulated in P-depleted, nitrate-grown cultures and with excess ambient ammonium. On the other hand, AmsxtI was expressed only when induced by P-depletion, suggesting that this gene may play an important role in P-recycling metabolism, while simultaneously enhancing toxin production.